Dermatitis caused by arthropods in domestic environment: an Italian multicentre study. (18th July 2017) - Stingeni, L.; Bianchi, L.; Hansel, K.; Neve, D.; Foti, C.; Corazza, M.; Bini, V.; Moretta, I.; Principato, M.
Abstract: Background: Skin diseases caused by mites and insects living in domestic environments have been rarely systematically studied. Objectives: To study patients with dermatitis induced by arthropods in domestic environment describing their clinical features, isolating culprit arthropods and relating the clinical features to the parasitological data. Methods: The study was performed in 105 subjects with clinical and anamnestic data compatible with the differential diagnosis of ectoparasitoses in domestic environments. Clinical data and arthropods findings obtained by indoor dust direct examination were studied. Results: Indoor dust direct examination demonstrated possible arthropods infestation in 98 subjects (93.3%), more frequently mites (56.1%) (mainly Pyemotes ventricosus and Glycyphagus domesticus ) than insects (43.9%) (mainly Formicidae and Bethylidae). Strophulus (46.9%) and urticaria‐like eruption (36.7%) in upper limbs and trunk with severe extent were prevalent. Itch was mostly severe (66.3%) and continuous (55.1%). Ectoparasitoses occurred frequently with acute course in summer (44.9%) and spring (30.6%). Conclusions: Possible correlation between clinical and aetiological diagnosis of arthropods ectoparasitoses in domestic environments needs the close cooperation between dermatologist and parasitologist. This is crucial to successfully and definitely resolve skin lesions by eradicating the factors favouring infestation.